Cutaneous Rosai-Dorfman Disease – A Case Report and Review of Literature - Thomas, Shalu; Joseph, Dahlia; Napolean, Renny; Joseph, Elizabeth (Annals of Pathology and Laboratory Medicine, 2022)
Rosai–Dorfman disease (RDD), or Sinus Histiocytosis with Massive Lymphadenopathy (SHML) is a self-limiting, rare benign proliferative disorder of histiocytes in the lymph nodes with occasional extra-nodal involvement of the skin. Isolated Cutaneous Rosai-Dorfman disease(C-RDD) without node involvement is an exceedingly rare occurrence. Despite its unique characteristics, the diagnosis of Cutaneous Rosai Dorfman disease is hampered by its variable clinical presentation, misleading histopathological patterns, and the absence of lymphadenopathy. Herein we present a case report of Cutaneous Rosai-Dorfman disease without any lymph node involvement.